2014
DOI: 10.5888/pcd11.130291
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Food Environment of a Rural Community: Baseline Findings From the Heart of New Ulm Project, Minnesota, 2010–2011

Abstract: IntroductionChanges in the food environment in the United States during the past few decades have contributed to increased rates of obesity, diabetes, and heart disease. Improving the food environment may be an effective primary prevention strategy to address these rising disease rates. The purpose of this study was to assess the consumer food environment of a rural community with high rates of obesity and low levels of fruit and vegetable consumption. Findings were used to identify food environment interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 23 publications
(34 reference statements)
5
40
0
1
Order By: Relevance
“…Our findings are consistent with studies that have identified rural areas typically have smaller and fewer supermarkets which equates to less variety, poorer quality and higher prices than in urban areas [ 7 , 43 , 45 ]. In Australia, four major supermarket chains exist, only the smallest of these was present in this community, all food stores in this LGA would be considered small in an urban context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with studies that have identified rural areas typically have smaller and fewer supermarkets which equates to less variety, poorer quality and higher prices than in urban areas [ 7 , 43 , 45 ]. In Australia, four major supermarket chains exist, only the smallest of these was present in this community, all food stores in this LGA would be considered small in an urban context.…”
Section: Discussionsupporting
confidence: 92%
“…While NEMS tools have been used internationally across a variety of settings including rural environments [ 42 , 43 ], many have adapted the tool to local context thereby limiting direct comparability of these findings with our study. There are also no similar studies within Australia either measuring the food environment of a whole rural LGA or using the NEMS tools to undertake a comprehensive food environment audit.…”
Section: Discussionmentioning
confidence: 99%
“…ground truthing different types of food outlets, mapping the distribution chain, surveying food availability and affordability), and often includes a combination of both approaches. Multiple examples exist of the use of formative research to develop environmental interventions [1825]. Formative research is needed to identify core values for message development, audience segmentation, and identification of the best communications channels [2630].…”
Section: Key Literature Gaps and Areas For Future Researchmentioning
confidence: 99%
“…Many studies have examined the density of food outlets around schools and its relationship with obesity and diet quality (Austin et al, 2005, Kipke et al, 2007, Simon et al, 2008, Zenk and Powell, 2008, Davis and Carpenter, 2009, Larson and Story, 2009, Walton et al, 2009, Laska et al, 2010, Tester et al, 2010, Babey et al, 2011, Day and Pearce, 2011, Black and Day, 2012, Buck et al, 2013, Pereira et al, 2014, An and Sturm, 2012, Heroux et al, 2012, Laxer and Janssen, 2014, Tang et al, 2014). Schools are often a primary anchor for research related to youth as the environment around schools is likely to be experienced by youth on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have used the Nutritional Environment Measure Survey (NEMS) tool to document food and beverage products placement, price, and promotion within stores (Glanz et al, 2007, Saelens et al, 2007, Cannuscio et al, 2013, Pereira et al, 2014), few studies to our knowledge have focused on outdoor FB advertising on outlets and within the community in the United States (Hillier et al, 2009, Yancey et al, 2009, Hosler and Dharssi, 2011, Powell et al, 2012, Rimkus et al, 2013), and only a handful more have focused on areas outside of the United States (Maher et al, 2005, Kelly et al, 2008, Walton et al, 2009, Adams et al, 2011). Findings from this work suggest that there are a large number of unhealthy outdoor advertisements that do not reflect current dietary guidelines, while evidence appears to be mixed if unhealthy advertisements cluster in specific areas or among particular populations.…”
Section: Introductionmentioning
confidence: 99%